Penentuan Marker untuk Mempermudah Motion Tracking dalam Video - Barnea, Samson; Suyanto, M; Fatta, Hanif Al (STMIK Palangkaraya, 2018)
In the motion tracking is required a marker that will be easier to process this motion tracking, marker certainly has a shape, size and position that will help facilitate the process of this motion tracking. In this research will be done shooting a scene with an experiment with 3 types of marker form and each marker has 5 different sizes, then the results of the taking will be analyzed. From the results of the analysis will get the results of numbers that will show the highest number for what markers with what size can help the process of motion tracking, as well as position marker where the most frequently appear on the results of the marker position analysis later. This can be seen from the results of software analysis that will be used later. Keyword : CGI, marker , motion tracking